(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2023)
This paper is a research around an aspect of contemporary history of culture, regarding modern fascination for the primitive word and the search for the primitive through study of the artistic productions of the mentally ill. In my work this problem is analyzed by the point of view of the book of Robert Volmat L’art psychopathologique. L’art psyichopathologique is a remarkable example to observe the problem of primitivism in its connections with psychology, anthropology and philosophical research on artistic expression.